Tajemnica Pięćdziesiątnicy. Lektura liturgiczna wydarzenia biblijnego - Jeziorski, Sławomir (Verbum Vitae, 2020)
The event of Pentecost, described by Saint Luke in the Acts of the Apostles, is an event constantly celebrated by the Church. In order to express the content of this mystery, the Church uses many biblical and liturgical texts. The analysis of these allows us to understand how the Church comprehends the event of Pentecost as expressed in the current liturgy. This article goes back to several texts of the Pentecost Vigil Mass and tries to construct, in their light, a liturgical reading of the biblical event described by St. Luke. John’s pericope about living water (Jn 7,37-39) is, first, briefly analysed as to its content and structure, and then it is read in the light of the alleluiatic verse, the collect, and the communion antiphon. Such an analysis allows us to capture several characteristics of the mystery of Pentecost celebrated in the current liturgy of the Church.